Studies on the ecology of medical care: a comparative analysis in historical perspective, 1928-2018 - Hugo Spinelli; Andrés Trotta; Viviana Martinovich; Marcio Alazraqui (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
In the definition of health policies and decision-making on the part of health officials, there is often a prevailing separation between clinical practice, epidemiology, and public health. Although this division is naturalized from the viewpoint of hospitals and public agencies, it is artificial in the context of concrete territories and communities, where problems are not structured according to the fragmentation of knowledge, but rather express the complexities of the problems faced by individuals and population groups. In this context, this article compiles and analyzes studies on the ecology of medical care carried out between 1928 and 2018 that have revisited the pioneering study "The ecology of medical care" by White, Williams and Greenberg. The discussion is structured around three central issues: 1) recurrent themes in studies on the ecology of medical care; 2) health information systems and health surveys; and 3) the institutional hegemony of hospitals in the health field.